2014
DOI: 10.1155/2014/601250
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Protects the Immature Rabbit Heart against Ischemia and Reperfusion Injury: Impact on Functional Recovery and Histopathological Changes

Abstract: The general anesthetic propofol protects the adult heart against ischemia and reperfusion injury; however, its efficacy has not been investigated in the immature heart. This work, for the first time, investigates the cardioprotective efficacy of propofol at clinically relevant concentrations in the immature heart. Langendorff perfused rabbit hearts (7–12 days old) were exposed to 30 minutes' global normothermic ischemia followed by 40 minutes' reperfusion. Left ventricular developed pressure (LVDP) and coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
3
5
0
1
Order By: Relevance
“…14,46 Other investigators have suggested propofol itself may be protective and any incremental benefits of RIPC are too small to be detected. 47 Our analysis is congruent with these theories, as we observed a highly significant reduction in AKI in the subgroup of patients who did not receive propofol, despite no benefit in the overall cohort. In addition to the neuronal pathway, humoral-mediated pathways have also been described.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…14,46 Other investigators have suggested propofol itself may be protective and any incremental benefits of RIPC are too small to be detected. 47 Our analysis is congruent with these theories, as we observed a highly significant reduction in AKI in the subgroup of patients who did not receive propofol, despite no benefit in the overall cohort. In addition to the neuronal pathway, humoral-mediated pathways have also been described.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, propofol may disrupt mediators of the neuronal pathway and diminish the clinical benefits of RIPC when compared with isoflurane anesthesia . Other investigators have suggested propofol itself may be protective and any incremental benefits of RIPC are too small to be detected . Our analysis is congruent with these theories, as we observed a highly significant reduction in AKI in the subgroup of patients who did not receive propofol, despite no benefit in the overall cohort.…”
Section: Discussionsupporting
confidence: 85%
“…Similar mechanisms were seen in the protective effects of curcumin and intermedin [44] It was reported that propofol had anti-oxidative activity [45]. Propofol scavenges H 2 O 2 and reduces the formation of lipid peroxides [46], which validates in heart protection [47,48]. Hsu et al discovered that propofol attenuates lipopolysaccharide-induced reactive oxygen species production through suppression of NADPH oxidase in human alveolar epithelial cells [49].…”
Section: Discussionmentioning
confidence: 77%
“…To date, several mechanisms have been identified to involve in the complex pathophysiological processes of hepatic I/R injury, such as microcirculation dysfunction, excessive reactive oxygen species (ROS), calcium overload, and activation of Kupffer cells (Klune and Tsung, 2010). Recently, propofol has been found to have a protective effect in I/R injury in the heart, kidney, and liver with the antioxidant effects (Ye et al, 2012;Yingjie et al, 2015;Shirakawa et al, 2014). Although the precise mechanisms of hepatic I/R injury have not been illuminated clearly, researchers have developed numerous medicines and methods to attenuate hepatic I/R injury, including anesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol (2,6-dissopropyl phenol) is a rapid and short-acting general anesthetic and widely used in clinical anesthesia (Zhang et al, 2016). Recently, propofol has been found to have a protective effect in I/R injury in the heart, kidney, and liver with the antioxidant effects (Ye et al, 2012;Yingjie et al, 2015;Shirakawa et al, 2014). However, the molecular mechanism of propofol involving the antioxidant effects in hepatic I/R injury has been poorly understood.…”
Section: Introductionmentioning
confidence: 99%